Cultural Meaning, Advertising, and National Culture: A Four-Country Study. Issue 1 (1st January 2018) - Czarnecka, Barbara; Brennan, Ross; Keles, Serap
ABSTRACT: Cultural meaning transfer theory and GLOBE dimensions were employed in this comparative study to examine the extent to which cultural meaning presented in advertisements reflected national cultures of the target countries. Content analysis was applied to advertisements from four countries to investigate whether the use of advertising appeals presented in these advertisements mirrored variations in cultures as described by GLOBE Society Values. Results revealed that, in line with the hypotheses, there were similarities and differences in the use of appeals, and only some of them mirrored the cultural variations. GLOBE Society Values were more likely to predict the use of appeals than GLOBE Society Practices, but not for all appeals. Advertisers can draw on national cultures for cultural meanings to be used in advertisements only to a limited extent. It may be that advertisements mold rather than mirror societal values, or that only certain cultural traits are important for advertisers.